Differential incidence of gonadal apoptosis in triploid-induced male and female turbot (Scophthalmus maximus) - Cal, R. (Rosa); Terrones, J. (Jaime); Vidal, S.; Abaunza, P. (Pablo); Piferrer, F. (Aquaculture, 2014)
In order to further investigate the reproductive physiology of triploid turbot, Scophthalmus maximus, the gonadal development and the incidence of apoptosis were studied in diploid and triploid fish at up to 28 months of age. Within the period studied, diploid males completed the reproductive cycle and produced spermatozoa, while the most advanced cell type observed in triploid males was spermatids. In diploid females, preovulatory oocytes were observed, whereas in triploid females a nearly total meiosis blockade was evident with only a small number of oogonia achieving the perinucleolar oocyte stage. Testosterone levels in males were similar regardless of ploidy level with peaks observed immediately before the completion of spermatogenesis; however, peaks were advanced in triploids. Estradiol levels remained very low in triploid females. In diploid males, apoptosis was observed only at the start of spermatogenesis and during testicular regression. In contrast, triploid males had an overall higher rate of apoptotic cells which was constant throughout the reproductive cycle. In diploid females, few or no apoptotic cells were observed in contrast to triploid females where these numbers were markedly increased followed by an overall downward trend as oogenesis progressed. These data suggest that apoptosis plays a role in the control of germ cell number and fate and this regulatory mechanism is magnified in females bearing three sets of chromosome. Thus, the sex-related effects of triploidy on gonadal development in turbot, and likely in fish, include an increase in apoptosis, particularly in females. 2